Multilevel logistic regression analysis of factors associated with delivery care service utilization among childbearing women in Ethiopia - Gebrekrstos Zeru, Naod; Bedada Tolessa, Dechasa; Abdisa Fufa, Jaleta; Girma Fufa, Bonsa (Frontiers in Reproductive Health, 2023)
Delivery service utilization is one of the key and proven interventions to reduce maternal death during the child bearing. In Ethiopia, the utilization of health facilities for delivery service still at lower level. This study intends to model the determinant factors for the delivery care service utilization of childbearing mothers in Ethiopia using the 2016 Ethiopian demographic and health survey data. A cross-sectional study design was selected to assess factors associated with delivery care among mothers who had at least one child in the last five years before the survey aged 15-49 years in the data. Among these eligible mothers, 3052 (27.7%) mothers were received delivery service care from health professionals. The results of multilevel logistic regression indicated that age, place of residence, woman and partner's educational level, household wealth index, exposure to mass media, birth order number, contraceptive type and number of antenatal care visits were the most determinant factors for the delivery care service utilization of mothers in Ethiopia. Woman and partner's educational level, household wealth index, exposure to mass media and number of antenatal care visits had a positive association with delivery assistance whereas birth order had negative association. The findings of this study were valuable implications to support strategies and interventions to address delivery care service in Ethiopia.